Effects of Resistance Training on Interleukin-6 and Tumor Necrosis Factor-Alpha in Older Adults: A Systematic Review (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Inflammaging is a chronic low-grade inflammatory condition that contributes to sarcopenia and functional decline in older adults, primarily through elevated interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Resistance training has been proposed as a non-pharmacological strategy with potential anti-inflammatory effects. However, evidence from randomized controlled trials (RCTs) remains inconsistent. This systematic review aimed to examine the effects of resistance training on IL-6 and TNF-α levels in adults aged ≥60 years. The review was conducted in accordance with PRISMA guidelines employing a narrative synthesis approach. RCTs published between 2010 and 2024 were retrieved from PubMed, Cochrane, and Scopus. Eight RCTs met the inclusion criteria. Four studies (50%) reported significant reductions in IL-6, while five studies (62.5%) demonstrated significant reductions in TNF-α. Pure resistance training showed greater consistency in reducing TNF-α compared to IL-6. Effective training protocols typically lasted 8–24 weeks, with a frequency of 2–3 sessions per week and intensities ranging from 60–80% of one-repetition maximum (1RM). Resistance training appears to be effective in attenuating inflammatory biomarkers in older adults, particularly TNF-α. However, outcomes are influenced by exercise modality, duration, intensity, and participant characteristics. Further studies using standardized protocols and longer follow-up periods are warranted.